The ethnoculture of the nogai turks and the nomadic heritage of the western kipchaks (Journal of Philosophy Culture and Political Science, 2023)
Abstract. The purpose of the article is to study the ethnocultural nomadic code of the Nogai Turks in the Middle Ages, to consider the concept of the «perfect man» in Turkic philosophy. The article discusses a new typology of the main archetypes of the perfect man of the Great Steppe. Scientific principles based on cultural symbols will be proposed to improve the cultural and philosophical systematization of the spiritual values of the modern Turkic world. In the modern world, where large-scale changes are taking place, the importance of the processes of globalization and the unification of cultures is increasing. In this regard, of particular importance is the consideration of the sources of spiritual revival, as well as the revision of the priorities of the mechanisms of cultural development of the Turkic peoples, the preservation in general of the unique and unique fundamental spiritual values of the Turkic ethnic culture. It is concluded that Turkic-speaking thinkers have always sought to form a full-fledged philosophical image of the individual. The philosophical approach to humanity presupposes the definition of the essence of the world and the concrete historical definition of the main forms of its activity, the disclosure of various historical types of being in it. The anthropocentric philosophy of the Eurasian wise thinkers who lived in the Middle Ages reveals the place of humanity in the world and its attitude to the world, analyzes the questions of who a person can be, realizing their capabilities, what is the ratio of the holy and sacred. This is the goal that is the «perfect person».The research work used works not only on philosophy, history, cultural studies, but also in other fields of knowledge, such as mythology, aesthetics, ethnography, as there was a need to give a complete picture of the ancient history and culture of the Nogai people.  The main nodes were reflected, firstly, in folk legends and beliefs, customs, customs, etc., which were the basis of ideological views, were reflected in descriptions of the Nogai world.Keywords: Turkic Nogai culture, Golden Horde civilization, Desht-Kipchak, nomadism, the Middle Ages, the Great Silk Road